2019
DOI: 10.1103/physrevlett.122.174502
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Vortex-Particle Complexes Bound to the Free Surface of Superfluid Helium

Abstract: We present an experimental and theoretical study of the 2D dynamics of electrically charged nanoparticles trapped under a free surface of superfluid helium in a static vertical electric field. We focus on the dynamics of particles driven by the interaction with quantized vortices terminating at the free surface. We identify two types of particle trajectories and the associated vortex structures: vertical linear vortices pinned at the bottom of the container and half-ring vortices travelling along the free surf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…45 This situation can arise both in bulk 46 and under a free surface of superfluid helium. 47 At a temperature of 1.6 K the viscosity of liquid helium is 1.3 Â 10 À6 Pa s. 48 Of course, for a realistic description of particle motion under such conditions, the 'particle-quantum vortex' interaction must be taken into account. 49 However, using our simple (non-quantum) formalism, we can estimate that the momentum relaxation time of such a particle with R = 10 mm can be t p = (2/9)R 2 r/Z B 20 ms and the inertial delay number b can be B10 5 .…”
Section: Discussionmentioning
confidence: 99%
“…45 This situation can arise both in bulk 46 and under a free surface of superfluid helium. 47 At a temperature of 1.6 K the viscosity of liquid helium is 1.3 Â 10 À6 Pa s. 48 Of course, for a realistic description of particle motion under such conditions, the 'particle-quantum vortex' interaction must be taken into account. 49 However, using our simple (non-quantum) formalism, we can estimate that the momentum relaxation time of such a particle with R = 10 mm can be t p = (2/9)R 2 r/Z B 20 ms and the inertial delay number b can be B10 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The large heat capacity ensures that any nanomaterial injected into the superfluid helium is quickly cooled and thermalized. This enables exploring the unprecedented interactions between quantum fluids and classical nanomaterials and nanoscopic quantum hydrodynamic effects (1)(2)(3). A major obstacle in such approaches is the lack of experimental techniques to suspend/levitate the target nanoobject in quantum fluid, and controlling and probing the object motion precisely.…”
Section: Introductionmentioning
confidence: 99%
“…A stunning example is the visualization of quantised vortex dynamics using frozen hydrogen particles [10,15]. However, although some reports have indicated that dense materials such as metallic or semiconducting nanowires are formed along the quantised vortex core [5,[16][17][18], the contribution of the quantised vortex remains controversial [5,12]. Herein, we provide direct experimental evidence of dense silicon nanoparticle attraction to the quantised vortex, and the stabilisation along the vortex core.…”
Section: Introductionmentioning
confidence: 88%